Contrast-Enhanced 3D-FLAIR Imaging of the Optic Nerve and Optic Nerve Head: Novel Neuroimaging Findings of Idiopathic Intracranial Hypertension - Golden, E.; Krivochenitser, R.; Mathews, N.; Longhurst, C.; Chen, Y.; Yu, J.-P.J.; Kennedy, T.A. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: The sensitivity of contrast-enhanced 3D-FLAIR has not been assessed in patients with idiopathic intracranial hypertension. The purpose of this study was to evaluate whether hyperintensity of the optic nerve/optic nerve head on contrast-enhanced 3D-FLAIR imaging is associated with papilledema in patients with idiopathic intracranial hypertension.MATERIALS AND METHODS: A retrospective review was conducted from 2012 to 2015 of patients with clinically diagnosed idiopathic intracranial hypertension and age- and sex-matched controls who had MR imaging with contrast-enhanced 3D-FLAIR. Two neuroradiologists graded each optic nerve/optic nerve head on a scale of 0–3. This grade was then correlated with the Frisén Scale, an ophthalmologic scale used for grading papilledema from 0 (normal) to 5 (severe edema). To estimate the correlation between the MR imaging and Frisén scores, we calculated the Kendall τ coefficient.RESULTS: Forty-six patients (3 men, 43 women) with idiopathic intracranial hypertension and 61 controls (5 men, 56 women) with normal findings on MR imaging were included in this study. For both eyes, there was moderate correlation between the 2 scales (right eye: τ = 0.47; 95% CI, 0.31–0.57; left eye: τ = 0.38; 95% CI, 0.24–0.49). Interreader reliability for MR imaging scores showed high interreader reliability (right eye: κ = 0.76; 95% CI, 0.55–0.88; left eye: κ = 0.87; 95% CI, 0.78–0.94). Contrast-enhanced 3D-FLAIR imaging correlates with the Frisén Scale for moderate-to-severe papilledema and less so for mild papilledema.CONCLUSIONS: Hyperintensity of the optic nerve/optic nerve head on contrast-enhanced 3D-FLAIR is sensitive for the detection of papilledema in patients with idiopathic intracranial hypertension, which may be useful when prompt diagnosis is crucial.CEcontrast-enhancedICPintracranial pressureIIHidiopathic intracranial hypertensionODright eyeONoptic nerveONHoptic nerve headOSleft eye